Acute exercise and children's cognitive functioning: What is the optimal dose of cognitive challenge?. (May 2023) - Anzeneder, Sofia; Zehnder, Cäcilia; Martin-Niedecken, Anna Lisa; Schmidt, Mirko; Benzing, Valentin
Abstract: Acute bouts of exercise have the potential to benefit children's cognition. Inconsistent evidence on the role of qualitative exercise task characteristics calls for further investigation of the cognitive challenge level in exercise. Thus, the study aim was to investigate which "dose" of cognitive challenge in acute exercise benefits children's cognition, also exploring the moderating role of individual characteristics. In a within-subject experimental design, 103 children ( M age  = 11.1, SD  = 0.9, 48% female) participated weekly in one of three 15-min exergames followed by an Attention Network task. Exergame sessions were designed to keep physical intensity constant (65% HRmax ) and to have different cognitive challenge levels (low, mid, high; adapted to the ongoing individual performance). ANOVAs performed on variables that reflect the individual functioning of attention networks revealed a significant effect of cognitive challenge on executive control efficiency (reaction time performances; p  = .014, ƞ 2 p  = .08), with better performances after the high-challenge condition compared to lower ones ( p s < .015), whereas alerting and orienting were unaffected by cognitive challenge ( p s > .05). ANOVAs performed on variables that reflect the interactive functioning of attention networks revealed that biological sex moderated cognitive challenge effects. For males only, the cognitive challenge level influenced the interactive functioning of executive control and orienting networks ( p  = .004; ƞ 2 p  = .07). Results suggest that an individualized and adaptive cognitively high-challenging bout of exercise is more beneficial to children's executive control than less challenging ones. For males, the cognitive challenge in an acute bout seems beneficial to maintain executive control efficiency also when spatial attention resources cannot be validly allocated in advance. Results are interpreted referring to the cognitive stimulation hypothesis and arousal theory. Highlights: An acute cognitively challenging bout of exercise benefited children's executive control. Compared to cognitively less challenging bouts, the high-challenging exercise fostered executive control the most. The cognitive challenge level of acute bouts of exercise did not affect alerting or orienting. Biological sex moderated acute exercise effects on the interactive functioning of executive control and orienting networks.